Investigation of a new lead-free Bi0.5(Na0.40K0.10)TiO3-(Ba0.7Sr0.3)TiO3 piezoelectric ceramic - Jaita P. (2014)
ABSTRACT: Lead-free piezoelectric compositions of the (1-x)Bi0.5(Na0.40K0.10)TiO3-x(Ba0.7Sr0.3)TiO3 system (when x = 0, 0.05, 0.10, 0.15, and 0.20) were fabricated using a solid-state mixed oxide method and sintered between 1,050°C and 1,175°C for 2 h. The effect of (Ba0.7Sr0.3)TiO3 [BST] content on phase, microstructure, and electrical properties was investigated. The optimum sintering temperature was 1,125°C at which all compositions had densities of at least 98% of their theoretical values. X-ray diffraction patterns that showed tetragonality were increased with the increasing BST. Scanning electron micrographs showed a slight reduction of grain size when BST was added. The addition of BST was also found to improve the dielectric and piezoelectric properties of the BNKT ceramic. A large room-temperature dielectric constant, εr (1,609), and piezoelectric coefficient, d33 (214 pC/N), were obtained at an optimal composition of x = 0.10.